Effect of salinity and pH on selected immune functions of the Indian white shrimp, Fenneropenaeus indicus (H. Milne Edwards, 1837) - Sharma, Krupesha; Jayaprakash, Seema; Philipose, K K; Radhakrishnan, E V (Indian Journal of Fisheries, 2016)
The Indian white shrimp, Fenneropenaeus indicus, was subjected to environmental stresses like high (9) and low (5.5) waterpH and decreasing water salinity (34 ‰ to 18 ‰) for a period of one week and certain vital immunological functions liketotal hemocyte count, total hemolymph protein and phenoloxidase activity were analysed to understand the effect of theenvironmental stress factors on these functions. The results indicated that while stress induced by change in the salinity hadno damaging effects on the immune functions, stress caused by lower water pH induced more immunological damage whencompared to higher water pH. Significantly decreased total hemocyte count and phenoloxidase activity were observed inshrimps exposed to lower pH when compared to shrimps exposed to higher pH and control shrimps. Also, lower pH significantlyreduced the hemolymph protein values. It is therefore concluded that Fenneropenaeus indicus that are exposed to extremepH show lowered immunological activity which would render the shrimp susceptible to infectious agents.